2019
DOI: 10.1038/s41598-019-50034-1
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus-induced IFNβ expression is NFκB-dependent and regulated by the macrophage microenvironment

Abstract: Macrophages play an important role in asthma pathogenesis both in the inflammatory and resolution phase of the disease. Macrophages can acquire different polarisation states dependent on their microenvironment. It is yet unclear through which mechanism the microenvironment affects the anti-viral response in macrophages. We hypothesized that the macrophage microenvironment regulates rhinovirus-induced IFNβ expression. Murine bone marrow-derived monocytes and human differentiated THP-1 cells were stimulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Our study supported this view: we found that IFNβ expression was consistently higher in NFκB1 −/− mice and, unlike in wild-type mice, was not reduced at exacerbation. This is in line with a previous study in which blocking of IκB kinase enhanced IFNβ expression in macrophages primed with Th2 cytokines [38]. We further demonstrated that enhanced expression of IFNβ in NFκB1-deficient mice at exacerbation was associated with an upregulation of antiviral signaling mediated by higher gene levels of IRF3 and IRF7.…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Our study supported this view: we found that IFNβ expression was consistently higher in NFκB1 −/− mice and, unlike in wild-type mice, was not reduced at exacerbation. This is in line with a previous study in which blocking of IκB kinase enhanced IFNβ expression in macrophages primed with Th2 cytokines [38]. We further demonstrated that enhanced expression of IFNβ in NFκB1-deficient mice at exacerbation was associated with an upregulation of antiviral signaling mediated by higher gene levels of IRF3 and IRF7.…”
Section: Discussion/conclusionsupporting
confidence: 93%
“…Immunomodulatory therapies target AMs that exist in multiple potential sites during a viral infection of the respiratory tract. In the case of rhinovirus infection, AMs can be M1/M2 polarized by GM-CSF/M-CSF or IFN-γ/IL-4 stimulation ( 86 , 87 ). M1/M2 herein can be likewise classified by their functions and origins rather than dichotomy.…”
Section: Prospect Of Ams As Target For the Treatment Of Ahr-related V...mentioning
confidence: 99%